2006
DOI: 10.1038/nm1355
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory actions of lipoxin A4 and aspirin-triggered lipoxin are SOCS-2 dependent

Abstract: Control of inflammation is crucial to prevent damage to the host during infection. Lipoxins and aspirin-triggered lipoxins are crucial modulators of proinflammatory responses; however, their intracellular mechanisms have not been completely elucidated. We previously showed that lipoxin A4 (LXA4) controls migration of dendritic cells (DCs) and production of interleukin (IL)-12 in vivo. In the absence of LXA4 biosynthetic pathways, the resulting uncontrolled inflammation during infection is lethal, despite patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
256
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(278 citation statements)
references
References 22 publications
17
256
2
3
Order By: Relevance
“…In the latter study, lipoxins were not found to induce IL-10 production and the actions of IL-10 in the system differed from those of lipoxins (13). Moreover, in a model of renal ischemia reperfusion injury in vivo, mice treated with the same analog used in this work displayed increased mRNA levels for SOCS-1 and SOCS-2 (42).…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 65%
See 2 more Smart Citations
“…In the latter study, lipoxins were not found to induce IL-10 production and the actions of IL-10 in the system differed from those of lipoxins (13). Moreover, in a model of renal ischemia reperfusion injury in vivo, mice treated with the same analog used in this work displayed increased mRNA levels for SOCS-1 and SOCS-2 (42).…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 65%
“…It has been recently reported that SOCS-2 is a critical intracellular regulator of the immunoregulatory and anti-inflammatory actions of lipoxins in mice infected with the intracellular parasite Toxoplasma gondii (13). In the latter study, lipoxins were not found to induce IL-10 production and the actions of IL-10 in the system differed from those of lipoxins (13).…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, it is necessary to further determine the dose-response characteristics of these ligands at the level of receptors and receptor-mediated signaling pathways. Finally, the FPR2/ALX-mediated agonistic activities of selected ligands appear to be indispensable for inducing anti-inflammatory proteins such as suppressor of cytokine signaling 2 (SOCS-2) as well as enhancing the proresolving functions of macrophages [42,43] . Consistent with these findings, FPR2/ALX has been shown to mediate different functions of LXA4 in neutrophils and macrophages [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Sera levels of lipoxin A4 rise during infection and remain high in chronic infection but lack of lipoxin A4 increases mortality following infection which may be cytokine mediated tissue injury [23,24]. Additionally, Toxoplasma lacks the ability to synthesize sterol for growth and replication and depends on the host blood cholesterol by scavenging the low-density lipoprotein receptors.…”
Section: Introductionmentioning
confidence: 99%